2008
DOI: 10.1002/cncr.23772
|View full text |Cite
|
Sign up to set email alerts
|

Optimal dose and schedule of an HER‐2/neu (E75) peptide vaccine to prevent breast cancer recurrence

Abstract: BACKGROUND.E75, a HER‐2/neu‐derived peptide, was administered as a preventive vaccine with granulocyte‐macrophage–colony‐stimulating factor (GM‐CSF) in disease‐free lymph node‐positive (NP) and lymph node‐negative (NN) breast cancer (BCa) patients. The optimal biologic dose (OBD) was determined based on toxicity and immunologic response.METHODS.Patients were vaccinated over 6 months (3, 4, or 6 times) with different doses of E75 plus GM‐CSF. Toxicities were graded per National Cancer Institute Common Terminolo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
27
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 50 publications
(29 citation statements)
references
References 55 publications
1
27
0
Order By: Relevance
“…Prepost -DTH responses were compared using unpaired two-tailed Student t test because node-positive patients did not have pre-DTH test done. A correlation between CD8 + E75-specific cells and DTH has been previously reported (30).…”
Section: Methodsmentioning
confidence: 65%
“…Prepost -DTH responses were compared using unpaired two-tailed Student t test because node-positive patients did not have pre-DTH test done. A correlation between CD8 + E75-specific cells and DTH has been previously reported (30).…”
Section: Methodsmentioning
confidence: 65%
“…In phase 1-2 trials with 3 different peptide vaccines, our group has observed that patients who required dose reduction because of large local reactions had significantly fewer recurrences than unvaccinated patients, suggesting a correlation between large local reaction and clinical response to vaccination. 31 Patients boosted at 6 months had significantly greater local reactions to the booster than those boosted later, indicating greater immune response to early boosting, presumably because of greater numbers or function of memory lymphocytes to vaccination. However, a limitation of local reactions is that they are generated in response to both the peptide and GM-CSF immunoadjuvant, unlike DTH measurements in response to small doses (100 lg) of the peptide alone performed prevaccination and at the completion of the primary series.…”
Section: At Present It Is Not Known What Threshold Level Of Antitumomentioning
confidence: 91%
“…17 Briefly, the HLA-A2:immunoglobulin (Ig) dimer (Pharmingen, San Diego, Calif) was loaded with the E75 or control peptide (folate binding protein peptide-E37 [25][26][27][28][29][30][31][32][33] RIA-WARTEL) by incubating 1 lg of dimer with an excess (5 lg) of peptide and 0.5 lg of b 2 -microglobulin (Sigma Chemical Co, St Louis, Mo) at 37 C overnight, then storing it at 4 C until used. PBMCs were washed and resuspended in Pharmingen Stain Buffer and were added at 5 Â 10 5 cells/100 lL/tube in 5 mL round-bottom polystyrene tubes (Becton Dickinson) and stained with the loaded dimers and antibodies as described previously.…”
Section: Hla-a2: Immunoglobulin Dimer Assaymentioning
confidence: 99%
“…As can be deduced from above, resection of the tumor mass may alleviate immune suppression allowing the use of immunotherapy to prevent new tumors to arise. Indeed, vaccination of patients with completely resected colorectal cancer metastases showed a significant survival advantage when compared to controls [37], whereas HER2 peptide vaccination in disease-free breast cancer patients was associated with a favourable trend for lower recurrences [38]. Unfortunately, this is not always the case as exemplified by a recent report on patients with surgically resected early stage non-small-cell lung cancer whom were vaccinated with MAGE-A3 but failed to show any improvement in disease free survival [39,40].…”
Section: Success Of Therapy At Early Stages Of Cancer or Minimal Resimentioning
confidence: 99%